Aluminum and acidity suppress microbial activity and biomass in acidic forest soils. (June 2016) - Kunito, Takashi; Isomura, Ikuko; Sumi, Hirotaka; Park, Ho-Dong; Toda, Hideshige; Otsuka, Shigeto; Nagaoka, Kazunari; Saeki, Kazutoshi; Senoo, Keishi
Abstract: To evaluate the effects of aluminum (Al) toxicity on microbial processes in acidic forest soils, we determined microbial biomass, soil enzyme activities associated with carbon (C), nitrogen, and phosphorus cycling (β-d -glucosidase and polyphenol oxidase, l -asparaginase, and acid phosphatase, respectively), exchangeable base cations, soluble and exchangeable Al (CaCl2 –Al and KCl–Al), and organically bound (Alp and Fep ) and both organically bound and noncrystalline forms (Alo and Feo ) of Al and iron (Fe) in Japanese forest soils (25 Inceptisols, seven allophanic Andisols, and eight nonallophanic Andisols). The exchangeable calcium (Ca) and magnesium (Mg) concentrations decreased significantly with decreasing soil pH. In contrast, the KCl–Al and CaCl2 –Al concentrations exponentially increased with decreasing pH, and the increase was steeper in Andisols than in Inceptisols. The Alp concentration also increased exponentially with decreasing soil pH in Andisols, and the Fep concentration increased in Andisols and Inceptisols, whereas the concentration of the noncrystalline Al pool (Alo  − Alp ) decreased with decreasing pH in Andisols. We showed that the β-d -glucosidase, polyphenol oxidase, and acid phosphatase activities were mainly suppressed by soluble and exchangeable Al, whereasl -asparaginase activity was depressed by soil pH. In Andisols, a negative effect of organically bound Al and Fe on the biomass C/organic C ratio was observed. These results suggest that Al toxicity and acidity repressed soil enzyme activities, leading to suppressed microbially mediated nutrient cycling, and that Al toxicity and a reduced availability of organic matter, as a result of Al and Fe binding, may protect a substantial pool of organic C from microbial degradation in acidic forest soils. Highlights: Soluble and exchangeable Al levels were elevated in acidic forest soils. Exchangeable Ca and Mg concentrations were lowered in acidic forest soils. Enzyme activities associated with C, N, and P cycling were suppressed by Al toxicity. By binding to organic matter, Al and Fe limit microbial biomass in Andisols.